Peran Pemoderasian Kompleksitas Tugas Pada Pengaruh Gaya Kepemimpinan Transformasional Terhadap Kemampuan Contextual Ambidexterity - Anwar Mansyur; Rangga Almahendra (Fakultas Ekonomi Universitas Islam 45, 2018)
Contextual ambidexterity is the behavioral capacity to integrate exploration and exploitation activities simultaneously. In knowledge management context, exploration is the same as knowledge acqusition activity, while exploitation is the same as knowledge sharing activity. In this study, the achievement of contextual ambidexterity will be analyzed at the individual level by looking at the effect of transformasional leadership, as well as the role of task complexity as the moderating variable by using path-goal theory and organizational learning theory as the theoretical foundation. The data is collected through a survey by distributing questionnaire to nurses that working in Rumah Sakit Pembina Kesejahteraan Umat Muhammadiyah, Yogyakarta. According to the criteria of the sample based on a purposive sampling, the total samples are 114 respondents. Then, it is analyzed using Moderated Regression Analysis techniques to test the hyphothesis. The results of this study indicates that transformational leadership has positive effect on the ability of contextual ambidexterity. The moderating effect test shows that the task complexity does not moderate the positive effect of transformational leadership on contextual ambidexterity.